(untitled) (Collection of scientific works «Modern structures of metal and wood», 2022)
The aim of the article is an experimental research of the influence of low-cycle sign- constant loading, as well as the most significant design factors on the deformability of steel reinforcement of reinforced concrete beams. In this regard, for experimental research, the authors developed a four-factor three-level Boxing plan B4. The experimental factors of the plan were varied according to the literature review, which showed that the most significant factors are the following: the value of the relative shear span a/h 0 , the concrete class C, the value (amount) of transverse reinforcement on the beams support sections ρ sw , the level of sign-constant loading η. The samples were tested according to the scheme of a single-span beam, alternately loaded with two centre-point forces. The number of cycles of sign-constant loading was accepted as 10. According to the results of the experiment, using the COMPEX program, adequate mathematical models of the deformations of steel reinforcement of reinforced concrete specimens- beams under the action of low-cycle sign-constant loading were derived, that reflect the influence of these factors both individually and in interaction with each other. Analyzing these models, the features of the development of tensile reinforcement in the specified conditions, were established. In particular, the factors that have the greatest influence on deformations are the relative shear span and the level of low-cycle loading. Thus, with their increase, the relative deformations of tensile reinforcement increase by 51% and 52%, accordingly, by series.